Heterometal doping on nickel selenide corrugations for solar-assisted electrocatalytic hydrogen evolution. Issue 40 (27th September 2022) - Chen, Weiwu; Qin, Zhaojun; Wang, Zhiming M.
Abstract : Inducing sunlight is an avenue for NiSe to be a better (HER) electrocatalyst. Abstract : Since nickel exhibits good binding energy and is inexpensive, it is widely applied as a hydrogen evolution reaction (HER) electrocatalyst. Among all Ni-based materials, nickel selenide (NiSe) shows a unique electronic structure as a semiconductor with good electrocatalytic activity. Herein, we prepare Co-doped NiSe (Ni1− x Co x Se) with a structure of uniform corrugations by one-step chemical vapor deposition. For comparison, Fe-doped NiSe (Ni1− x Fe x Se) and NiSe are also prepared using the same method. In alkaline electrolyte, Ni1− x Co x Se shows great HER performance in terms of low overpotential (93 mV@10 mA cm −2 and 140 mV@50 mA cm −2 ) and long-term stability. Moreover, with the assistance of solar energy, the overpotential needed for Ni1− x Co x Se is reduced, making Ni1− x Co x Se better than most reported NiSe-based HER catalysts. On the other hand, the current density of Ni1− x Co x Se is 13 mA cm −2 @93 mV and 63 mA cm −2 @140 mV with illumination, which is 30% and 26% higher than that without solar illumination assistance, respectively. Therefore, we believe that inducing sunlight to electrocatalytic hydrogen evolution in water splitting could be a supplementary footprint toward the utilization of solar energy.